Vidna elektrofiziologija pri otroku - Brecelj, Jelka (Zdravniški vestnik, 2005)
Background. Electrophysiological assessment of vision in children helps to recognise abnormal development of the visual system when it is still susceptible to medication and enventual correction. Visual electrophysiology provides information about the function of the retina (retinal pigment epithelium, cone and rod receptors, bipolar, amacrine, and ganglion cells), optic nerve, chiasmal and postchiasmal visual pathway, and visual cortex. Methods. Electroretinograms (ERG) and visual evoked potentials (VEP) are recorded non-invasively; in infants are recorded simultaneously ERG with skin electrodes, while in older children separately ERG with HK loop electrode in accordance with ISCEV (International Society for Clinical Electrophysiology ofVision) recommendations. Results. Clinical and electrophysiological changes in children with nystagmus, Lebers congenital amaurosis, achromatopsia, congenital stationary night blindness, progressive retinal dystrophies, optic nerve hypoplasia, albinism, achiasmia, optic neuritis and visual pathway tumours are presented. Conclusions. Electrophysiological tests can help to indicate the nature and the location of dysfunction in unclear ophthalmological and/or neurological cases.
Keywords: Albinism, Ocular; Albinizem očesni; Barvni vid, izpadi; Child; Color Vision Defects; diagnostika; Electroretinography; elektrofiziologija; Elektroretinografija; Evocirani potenciali vidni; Evoked Potentials, Visual; Night Blindness; Nočna slepota; Nystagmus; oftalmologija; Optic Atrophy; Optic Atrophy, Hereditary; Optic Neuritis; Optični nevritis; Optični živec, atrofija; otroci; Otrok; vid